2022
DOI: 10.3991/ijim.v16i22.36149
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Online Learning Media based on Tiktok for Teaching Local Wisdom Course during the Covid-19 Pandemic

Abstract: This research and development (R&D) study aims at utilizing a highly trending social media platform, TikTok, as an audio-visual online learning medium for South Sumatra’s local wisdom course in the History Education program of Universitas Sriwijaya. This study uses the ADDIE development model as its framework, framing the whole process in its five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subject chosen was History Education students at Universitas Sriwijaya. Two v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is interesting to use this application in English class, which can provide students who are considered as audio-visual learning. This result ties well with previous studies wherein TikTok is a practical and audio-visual online learning medium, which has a positive impact on students' learning performance (Syarifuddin & Sinta, 2022). Further informant answered a neutral response related to the question, which demonstrates in the below section.…”
Section: Findings and Discussionsupporting
confidence: 88%
“…It is interesting to use this application in English class, which can provide students who are considered as audio-visual learning. This result ties well with previous studies wherein TikTok is a practical and audio-visual online learning medium, which has a positive impact on students' learning performance (Syarifuddin & Sinta, 2022). Further informant answered a neutral response related to the question, which demonstrates in the below section.…”
Section: Findings and Discussionsupporting
confidence: 88%
“…Yang (2020) also added that the data in his research shows students gave a positive response to the use of social media TikTok in the EFL class because TikTok increased their interest and motivation to learn in learning English in the classroom. Syarifuddin & Sinta (2022) also confirmed that TikTok learning videos are good instructional material. TikTok's instructional media has a favorable effect on how well students succeed in terms of learning objectives.…”
Section: Introductionsupporting
confidence: 59%
“…According to a reference source obtained from the internet, Wikipedia, the TikTok app is a Chinese social network owned by ByteDance that was launched in 2017 for iOS and Android users in markets outside of China (Boffone, 2021;Syarifuddin, 2022). This application allows users to make or measure lip-sync videos 3 to 60 seconds long.…”
Section: Learning Music Through Social Media On the Tiktok Applicationmentioning
confidence: 99%